2018
DOI: 10.15537/smj.2018.11.23394
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus related discrimination in general dentistry

Abstract: Objectives:To investigate HIV related discrimination among general dentists in Jeddah, Saudi Arabia; and to list factors affecting or causing healthcare providers to discriminate people living with HIV (PLWH).Methods:The current study takes place in Jeddah, western Saudi Arabia. The duration for accepting all responses was between March and November, 2017. In this cross-sectional study, we used a self-administered, structured questionnaire. The sample size was 430 general dentists practicing in Jeddah, Saudi A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(33 reference statements)
0
10
0
5
Order By: Relevance
“…In addition, 100% reported double-glove use and that discrimination against these patients was 33% higher in private clinics than in government institutions. 28 In our study, 70% of patients perceived that dentists knew about HIV/AIDS, which does not necessarily reflect the level of knowledge that professionals may have. It is therefore suggested for future studies to compare what the patient perceives about the dentists' knowledge and the actual knowledge they have, since studies measuring these variables are lacking.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, 100% reported double-glove use and that discrimination against these patients was 33% higher in private clinics than in government institutions. 28 In our study, 70% of patients perceived that dentists knew about HIV/AIDS, which does not necessarily reflect the level of knowledge that professionals may have. It is therefore suggested for future studies to compare what the patient perceives about the dentists' knowledge and the actual knowledge they have, since studies measuring these variables are lacking.…”
Section: Discussionmentioning
confidence: 57%
“…Discrimination against patients with HIV/AIDS was also 33% higher in private practice than in government practice. Discriminatory attitudes reported by people living with HIV/AIDS by health care providers are refusal to care, unnecessary referrals, unfriendly care, and fear of infection [30].…”
Section: International Journal Of Dentistrymentioning
confidence: 99%
“…As such, these oral impacts are featured as a core element of the dental undergraduate curriculum. Despite the inclusion of HIV in the dental curriculum and current concepts such as universal cross infection control being evermore commonplace in dental practice, HIV stigma still persists among the dental profession (Acosta de Velásquez, Pérez‐Then, Mueses Marín, Pinzón Gómez, & Shor‐Posner, 2011; Alshouibi & AlAlyani, 2018; Arheiam et al., 2017; Crossley, 2004).…”
Section: How Does Hiv Stigma Manifest In the Dental Setting?mentioning
confidence: 99%
“…In China, almost half (44%) of dentists agreed that saliva was a vehicle for the transmission of HIV and more than three‐quarters (86%) wore extra personal protective equipment when treating PLHIV (Lee, Fan, Starr, & Dogon, 2017). Studies undertaken in North Africa and the Middle East suggested that there was concern from most dentists (81.5%) that transmission in the dental setting was very likely and there was a general uncertainty from the majority (82%) about their willingness to provide care for PLHIV (Alshouibi & AlAlyani, 2018; Arheiam et al., 2017). In Saudi Arabia, more than two‐thirds (67.4%) of dentists agreed to some form of HIV discrimination and did not have the confidence to provide surgical dental treatments to PLHIV; furthermore, more than half did not have the confidence to provide routine, non‐surgical dental procedures.…”
Section: How Does Hiv Stigma Manifest In the Dental Setting?mentioning
confidence: 99%